2013
DOI: 10.1007/s15010-013-0499-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health services for people living with HIV/AIDS in Germany: are we up to the challenge?

Abstract: Many PLHIV consult their HIV-physician regularly for medical follow-up and also indicate that HIV-physicians should be the source of information concerning SRH counselling. HIV-physicians should take advantage of their key role in HIV care and strengthen their efforts to integrate SRH services in routine HIV care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Much of the above-mentioned contrast between syphilis and CT/NG testing coverage may stem from physician’s lack of time and discomfort with sexual history taking and collection of STI swabs [ 20 , 21 ]. A survey analyzing the patients’ satisfaction with sexual and reproductive health (SRH) services in HIV primary care identified shortage of time, a lack of service providers’ initiative, and patients’ difficulty to address SRH topics as most relevant hindering factors for satisfying SRH services [ 22 ]. Structural or systems level interventions appear to be more effective and sustainable to improve STI screening rates than interventions on patients or clinicians level [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the above-mentioned contrast between syphilis and CT/NG testing coverage may stem from physician’s lack of time and discomfort with sexual history taking and collection of STI swabs [ 20 , 21 ]. A survey analyzing the patients’ satisfaction with sexual and reproductive health (SRH) services in HIV primary care identified shortage of time, a lack of service providers’ initiative, and patients’ difficulty to address SRH topics as most relevant hindering factors for satisfying SRH services [ 22 ]. Structural or systems level interventions appear to be more effective and sustainable to improve STI screening rates than interventions on patients or clinicians level [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a European multicenter study found that 42% of 705 sexually active, HIV-positive MSM in 14 European countries reported at least 1 occasion of unprotected vaginal or anal intercourse with a casual partner in the previous 6 months. 5 , 6 The European MSM internet survey, an online survey with more than 180,000 MSM from 38 European countries participating, reported that almost twice as many HIV-positive MSM had unprotected sexual encounters with casual partners, compared with HIV-negative, and untested MSM. 7…”
Section: Introductionmentioning
confidence: 99%